Pouvoir politique et pouvoir religieux. L’exploitation de la Sanusiyya au sein de la Libye indépendante (1951-1958) - Carlotta Marchi (L’Année du Maghreb)
The United Kingdom of Libya, established on 24 December 1951 under the crown of Idris al-Sanusi, found its legitimacy in Islam according to the way of the Sanusiyya, a religious Sufi brotherhood founded near Mecca in 1837, which had its centre of religious expansion in the Cyrenaic hinterland, and which became, during the 20th century, one of the symbols of the resistance to colonialism. Based on the examination of European archival sources, this paper aims to reconstruct the process of metamorphosis and exploitation of the Sanusiyya within the United Kingdom of Libya from 1951 to 1958, as well as to study its causes and consequences and its role as instrument of political legitimisation within the reign. Indeed, in the case of independent Libya, it can be argued that the Sanussi Islam represented a form of political power management within the national-state paradigm. Likewise, as the source of political legitimisation of independent Libya, the Sanusiyya underwent a process of bureaucratisation, i.e. an institutional degeneration whose sole purpose was the preservation of power.Starting with a brief overview of the organisation of political power in independent Libya, the essay develops by focusing, in the second and third paragraphs, on concrete examples that testify the exploitation of religion for political purposes made by the King, by the descendant branches of the Sanusiyya, and by personalities linked to the ṭarīqa through religious affiliation. The exploitation of the Sanusiyya, in fact, took place through the instrumentalisation of the ṭarīqa’s past (anniversaries, celebrations), through the reconstitution of its religious network, as well as through the exploitation of the Sanusiyya membership, in order to obtain a political position in the State, or, in a more general way, some kind of power. These elements were exploited in the management of internal political affairs, such as educational matters, as well as for the foreign policy, in opposition to the ideals of Arab nationalism and Nasserism that were flourishing during the 1950s and penetrated the Kingdom from the Egyptian border, particularly through the educational sector. All these elements eventually sanctioned the decline of the social and religious distinction of the Sanusiyya within independent Libya, as well as a process of bureaucratisation.It can be said that, in the 1950s, Islam according to the way of the Sanusiyya and the reconstruction of its structure became the “barycentre of the new state”. Nevertheless, they lost their autonomy and were subjected to an extreme phenomenon of political exploitation implemented by the monarchy and, more in general, by the state itself. The ṭarīqa thus appeared to be a political instrument used at different levels: the result was a profound devaluation of its traditional role in society, which was experienced by the younger generation. Consequently, although it was the basis on which the independent Libya was built and legitimised, the Sanusiyya and its idea of Islam remained dependent on the state, which resulted in their transformation into an administrative apparatus. The change of the Sanusiyya within the State was thus defined by a combination of causes, first and foremost the political positioning of its šayḫ in the new Libya and the definition of a new functionality for the ṭarīqa. Whereas in the past the success of the Sanusiyya had depended on a precise autonomy toward the imperial structure of the Ottoman and colonial empires, so that the figure of the šayḫ was functional for the preservation of the Sufi Way and the transmission of Islamic knowledge, the political legitimisation of his function, as emir and king, led to a redefinition of the whole structure of the ṭarīqa. Hence, in the Libyan case, the establishment of a nation-state, built on and legitimised by the ṭarīqa, radically changed the structure and function of a religious institution, decreeing an adaptation to a model that was no longer theocentric but theocratic. The clash with a modern State model, built on the ṭarīqa and legitimised by it, also changed the function of Islam in relation to the State itself. It is therefore possible to argue that, within independent Libya, occurred a process of change and bureaucratisation for the Sanusiyya, to the extent that the ṭarīqa found itself acting within a new institutional framework that the brotherhood itself had helped to create and consolidate, by guaranteeing a political legitimacy based on religious assumptions.